2018
DOI: 10.21500/20112084.1777
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Behavior, Parental Conflict and Community Violence in Students with Aggressive Behavior

Abstract: The effects of the presence of challenging behavior problems, parental conflict and violence in the community were determined by the probability of occurrence of bullying behaviors in elementary students. 664 students participated in the study, of whom 80 (12.04%) were identified as aggressors. 80 students with no reports of attacks were later selected randomly for comparison. Using logistic regression, it was found that the variables studied manifest significant differences between the student groups with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Nevertheless, to our knowledge, only a few studies have investigated the predicting role of community violence exposure on school bullying. Some studies, without distinguishing the differential effects of community violence witnessing and victimization, found a significant association between violence exposure within the community and bullying perpetration [21,47], over and above other socioenvironmental factors, such as poverty, inequality and political violence [48]. A seminal cross-sectional study by Schwartz and Proctor [49] found that children who had been a witness to or victim of community violence were more likely to bully their classmates.…”
Section: Exposure To Community Violence and Involvement In School Bulmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to our knowledge, only a few studies have investigated the predicting role of community violence exposure on school bullying. Some studies, without distinguishing the differential effects of community violence witnessing and victimization, found a significant association between violence exposure within the community and bullying perpetration [21,47], over and above other socioenvironmental factors, such as poverty, inequality and political violence [48]. A seminal cross-sectional study by Schwartz and Proctor [49] found that children who had been a witness to or victim of community violence were more likely to bully their classmates.…”
Section: Exposure To Community Violence and Involvement In School Bulmentioning
confidence: 99%
“…Generally, higher rates of bullying are found in communities in which violence is modeled and/or condoned, although the causal nature of these relationships remains unclear [14]. While there is a strong evidence that both exposure to community violence (e.g., [15][16][17]) and self-serving CDs [18,19] are associated with externalizing behaviors (i.e., aggression, conduct problems, delinquency), only a few studies (e.g., [20,21]), to our knowledge, have systematically examined how bullying behavior (as a specific subtype of aggression) is influenced by experiences of community violence exposure. Moreover, only one study [22] has investigated the associations of CDs, according to the Gibbs' model, with the involvement in bullying behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, and unlike the high-order ones (whose study is advisable rather from young adulthood), this personality trait has been remarked as a major issue for adolescent behavior throughout the previous literature. In this regard, there are some applied studies on bullying [ 28 , 29 ] endorsing the assumption that high-sensation seeking adolescents (but especially males) get more frequently engaged in active bullying dynamics, as well as in other harmful behaviors, including substance use [ 66 ], cybernetic bullying [ 67 ], and extra-school aggression [ 29 , 50 ]. ICT interaction.…”
Section: Discussionmentioning
confidence: 99%
“… Literature-based demographic and psychosocial predictors of bullying would significantly explain peer-to-peer intimidation scores. This assumption is based on a series of commonly significant bullying predictors documented in the empirical literature, including sensation seeking, family conflict, and psychological health issues, such as distress, and life satisfaction [ 2 , 26 , 29 , 49 , 50 ]. …”
Section: Introductionmentioning
confidence: 99%
“…An outstanding aspect of this lies in the role that is given to certain vital experiences that can mark the transition towards the ideation of and attempt of suicide (Joiner, 2009). The experiences of the adolescents in violent situations and victimization, fundamentally at school, are of particular relevance to our study, both of which must be analyzed from an ecological perspective (Valdés Cuervo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%